Hardy the Physician - Fincham, T. author. aut Link
XII, 266 p.
Keywords: Was Thomas Hardy clinically depressed or just syphilitic? Was Egdon Heath imbued with melancholic vapours? And does this explain why many of his characters suffered from depression, took their own lives or developed homicidal tendencies? This book by a rural GP explores these and many other medical issues in Hardy's life and works.